EFFECT OF HYDROGEN ON THE DEVELOPMENT OF JOINTING IN CARBONATE ROCK - Levshunova S.P. (My University, 1988)
After establishing the ability of hydrogen to form solid solutions in limestone, the change in mechanical properties of the limestone was elevated. Blocks of Podolian dolomitized limestone that had previously been used to study the occurrence of hydrogen solid solutions were used. The experiments indicate that, as in metals, hydrogen taken up by limestone changes its mechanical properties and increases its brittleness. When it is adsorbed by limestone, hydrogen not only hydrogenates the organic matter contained in it, promoting generation of hydrocarbons, but also changes its mechanical properties, promoting hydrogen embrittlement and increased jointing of the matrix limestone.